Exploring the Application of “Internet Medical” to Epidemic Prevention and Control on Chinese Campus in the Post-Epidemic Era - Ke C; Zhang F (Dove Medical Press, 2023)
Chunliang Ke, Faqing Zhang Guangdong University of Petrochemical Technology, Maoming, People's Republic of ChinaCorrespondence: Faqing Zhang, Guangdong University of Petrochemical Technology, No. 139 Guandu Road, Maonan District, Maoming, 525000, People's Republic of China, Tel +8613437565771, Email jiaoshidi@163.comAbstract: China has entered the post-epidemic era with the implementation of a general program for epidemic prevention and control of Category B infectious diseases. The number of sick people in the community will increase dramatically over a period of time, which will inevitably lead to a run on hospital medical resources. Schools, as one of the key institutions in epidemic disease prevention, will face a major test of their medical service system. The "Internet Medical" will be seen as a new way for students and teachers to access medical services, providing them with the convenience of remote consultation, interrogation, and treatment. However, there are many problems with its use on campus. In this regard, this paper aims to identify and evaluate the problems in the interface of the "Internet Medical" service model on campus, intending to improve the current level of medical services on campus and ensuring the safety of students and teachers on campus.Keywords: post-epidemic era, campus, internet medical, disease prevention